Influence of trunk extension technique on performance and core stability during ergometer rowing - Ertel, G.; Simon, F.; Duchene, Y.; Maciejewski, H.; Gauchard, G.; Mornieux, G. (ISBS - Conference Proceedings Archive (Konstanz), 2022)
This study had for purpose to evaluate the impact of using a different timing of trunk extension on performance parameters and on core stability during ergometer rowing. 16 expert rowers took part in this study. Each subject rowed with 3 different trunk extension timings on a RowPerfect 3. An early trunk extension technique was detrimental to performance and induced more activity of trunk extensors. The usual legs-trunk-arms kinematics sequence seems to be more performant despite not being the least demanding on core stability.